Resource tests of face packing seals with reversible grooves - Гудков, Сергей Николаевич; Загорулько, Андрей Васильевич (Technology audit and production reserves, 2015)
The analysis of existing designs of face mechanical, stuffing box packing and hydrodynamic seals, as well as methods for experimental determination of physical and mechanical properties of packings and hermetic sealing of the seal unit, that allowed to do the conclusion about the relevance of investigation and development of new face packing seal designs was conducted. The face packing seal design with reversible grooves, allowing due to hydrodynamic unloading of friction pair and return pumping of flow in sealed medium, to reduce the leakage value, friction and wear, as well as significantly expand the operating parameters (sealed pressure and sliding velocity) of friction pair was created. The investigations have shown that the seal can be guaranteed used at sealed liquid pressures to 2 MPa, providing minimal leakages and allowed thermal state of the seal unit. Resource tests have confirmed the working capacity, hermetic sealing and durability of the new seal design that can be used for pumps of general industrial purpose, pumping chemical and neutral fluids.